The mental condition of Polish adolescents during the COVID-19 pandemic and war in Ukraine - Wójtowicz-Szefler, Małgorzata; Grzankowska, Izabela; Deja, Monika (Frontiers in Public Health, 2023)
Recently, the experience of the COVID-19 global pandemic has significantly affected the mental condition of entire societies by increasing anxiety and stress resulting from its sudden and completely unexpected nature. In Poland, apart from the pandemic, there is an ongoing threat of an armed conflict just across the border, which can constitute direct and indirect threats to physical and mental health. Each of these situations is unusual and difficult. It is also in sharp contrast to the developmental needs of children and adolescents. It especially violates the principal need of this developmental period, which is to grow up in a predictable as well as physically and emotionally safe environment. The purpose of the conducted research was to assess the psychological condition of Polish adolescents, whose social situation is difficult, in order to take appropriate preventive measures based on this assessment. The study was conducted using the "Who are You?" Scale of Transparency Anxiety and the Revised Child Anxiety and Depression Scale (RCADS), as well as a researcher-made survey containing questions about well-being in relation to the pandemic, distance learning and the ongoing war in a neighbouring country. Approval was obtained from the Bioethics Committee to conduct the projected research. The study included 945 adolescents aged 11 to 15 (M=13.10; SD=1.11) making a representative sample of adolescents from 14 regions in Poland. The results of the research and analyses show that the adolescents under study have a medium level of intensity of neuroticism, with the highest levels occurring in adolescents aged 14. Moreover, the adolescents manifest relatively lower symptoms of anxiety and depression as well as concern about the pandemic and the war in Ukraine than expected.